Challenges in the Implementation of Clinical Pathway in Indonesia: A Systematic Review - Akhlia Ayu Helzainka (Cermin Dunia Kedokteran, 2021)
Backgrounds: Clinical Pathway (CP) is a tool that consists of practical treatment processes to implement clinical guidelines to improve the quality of services. This review is to describe challenges faced by hospitals in implementing clinical pathways. Methods: This systematic review uses Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) protocols. Articles were searched in Portal Garuda, Google Scholar, and the University of Indonesia online library. The final nine articles were included for qualitative synthesis. Results: Eleven hospitals were identified from 9 articles reviewed. Factors found to influence CP implementation were then divided into five major groups. Conclusions: The main factors affecting CP implementation in hospitals in Indonesia are human resources and hospital leadership and management. Supporting facilities of CP implementation, monitoring and evaluation, and user-friendly CP template are also factors that have to be noticed by hospitals in Indonesia to ensure the quality of services. Latar Belakang: Clinical Pathway (CP) adalah alat proses praktis yang merinci penerapan pedoman klinis untuk meningkatkan kualitas pelayanan. Tujuan kajian ini adalah untuk menggambarkan faktor-faktor yang memengaruhi proses implementasi CP di rumah sakit di Indonesia. Metode: Tinjauan sistematis ini menggunakan protokol Preferred reporting items for systematic review and meta-analysis (PRISMA). Sumber artikel berasal dari Portal Garuda, Google Scholar, dan perpustakaan online Universitas Indonesia. Sejumlah 9 artikel disertakan dalam sintesis kualitatif. Hasil: Terdapat 11 rumah sakit yang diidentifikasi dari 9 artikel yang dikaji. Faktor-faktor yang ditemukan memengaruhi implementasi CP di 11 rumah sakit kemudian dibagi menjadi 5 kelompok besar. Simpulan: Faktor utama di rumah sakit di Indonesia yang memengaruhi implementasi CP adalah kepemimpinan dan manajemen rumah sakit serta aspek sumber daya manusia. Dukungan sarana dan prasarana, monitoring dan evaluasi, serta formulir CP yang mudah digunakan juga menjadi faktor yang harus diperhatikan untuk memastikan kualitas layanan.